Pengaruh Citra Merek, Kualitas Produk, Persepsi HargaDan Iklan Terhadap Kepuasan Pengguna Sepeda Motor Honda Beat (Studi Pada Mahasiswa FEB Universitas Stikubank Semarang) - Ticha Tiwi, 14.05.51.0146; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2019)
The purpose of this study is to describe and analyze the influence of brand image, product quality, price perception and advertising on customer satisfaction (case study of FEB students at Stikubank University Semarang). In this study the independent variables that affect customer satisfaction are limited to variable brand image, product quality, price perception, and advertising. The population in this study were all Economics and Business Faculty students at the Stikubank University Semarang. And 100 respondents were chosen who used Honda Beat as the sample. The data testing techniques used included the Validity Test with factor analysis, the reliability test with Cronbach alpha, multiple linear regression analysis, and test the significance of the coefficient of determination to prove the truth of the hypothesis. The test results obtained that there is no significant effect of Brand Image variables on customer satisfaction. There is a significant effect on product quality variables on customer satisfaction. There is no significant effect of price perception variables on customer satisfaction. There is a significant effect of advertising variables on customer satisfaction.